Cardiac surgery and hypertension: a dangerous association that must be well known - Yuan,Shi-Min (2011)
It is well-known that hypertension is a very common disease, and severe cerebrovascular accidents might occur if the blood pressure is not properly controlled. However, conditions associated with uncontrolled hypertension may be overlooked, and may become critical and eventually require a surgical intervention on an urgent basis. Coronary artery disease, acute aortic syndrome, congenital and valvular heart disease, and arrhythmias are under this topic of discussion. Of them, coronary artery disease including myocardial infarction and especially postinfarction myocardial rupture, and aortic dissection are major critical situations that physicians may encounter in clinical practice. The role that hypertension plays in these conditions can be complex, including hemodynamic, electrophysiological and biomolecular factors, where the latter may prevail in the current era. Coronary artery disease may be associated with a reduced nitric oxide synthesis. Transforming growth factor and matrix metalloproteinases have been observed in relation to aortic syndrome. Wnt, p38 and JNK signaling pathway may be involved in the development of ventricular hypertrophy responsible for cardiac arrythmias. Various gene phynotypes may present in different congenital heart defects. This article is to present these conditions, and to further discuss the possible etiologies and the potential treatment strategies so as to highlight the relevance at a prognostic level.